Perception towards mammogram among female school teachers in Almashoor Islamic Girls School, Penang - Latif, Norsaudah Abdul (Universiti Sains Malaysia, 2009)
Mammogram is very effective in identifying most breast cancer in all age groups. Mammogram has been proven to reduce mortality from breast cancer especially for women in age between 40 to 69. The objectives of this study were to identify the level of knowledge towards mammogram among female school teachers and to determine the attitude towards mammogram among female school teachers. This is a cross-sectional study conducted among 36 female school teachers at Almashoor Islamic Girls School from February 2009 to March 2009 using self-report questionnaires. Microsoft Statistical Package for Social Science (SPSS) version 12 was utilized to assess demographic data, level of knowledge towards mammogram and attitude towards mammogram among female school teachers. The results demonstrated that 96.8% of female school teachers have average knowledge towards mammogram. Majority of female school teachers (54.8%) have positive attitude towards mammogram. The statistical test reflected that there was no correlation between attitude towards mammogram and level of knowledge towards mammogram among female school teachers. This study revealed that the level of knowledge towards mammogram is average among female school teachers in Almashoor Islamic Girls School, Penang. However, the attitude towards mammogram among female school teachers is positive. Therefore, more health education programs or campaigns need to be done to enhance the knowledge towards mammogram.